Wireless mesh networking : implementation of internet of things system - Ji, Xiang (2016)
Wireless sensor networks are capable of gathering large quantities of distributed multipoint data that could be used to analyse and study the behaviour of our surroundings or environmental changes. However, its capabilities are largely limited by the rationing of power supply when deployed outdoors. Processing and radio transmission power have to be reduced in order to lengthen the lifespan of the sensor nodes which are operating on batteries as much as possible. This poses difficulties with scaling up the wireless sensor network as it would mean more packet transmission hops and wireless radio power required to expand its area of coverage.